The Impact of Artificial Intelligence on Copyright Law in Uganda - Harmony Leaticia Uweera (Uganda Christian University, 2024)
The study evaluates artificial intelligence (AI)’s impact on copyright law, addressing issues of authorship challenges, infringement issues, and joint works involving AI. The study explores how AI-generated content complicates traditional copyright definitions and enforcement mechanisms. By reviewing related and relevant literature from various sources, it identifies the gaps and loopholes in the current policies and proposes adjustments to align with AI advancements. The study aims to guide lawmakers, to enhance understanding in this field, and also offer policy recommendations for addressing AI-related copyright challenges. The key and major concerns addressed include determining authorship in AI-generated works, addressing copyright infringement, and clarifying ownership arrangements in joint works involving AI. Ethical considerations regarding user consent and data collection on AI platforms are also highlighted. Ultimately, the study seeks to inform and guide future policy discussions and also shape future strategies for effective copyright enforcement in the age of AI.